LncRNA FENDRR in Carcinoma-Associated Fibroblasts Regulates the Angiogenesis of Oral Squamous Cell Carcinoma Through the PI3K/AKT Pathway - Xu, Yuming; Jiang, Erhui; Shao, Zhe; Shang, Zhengjun (Frontiers in Oncology, 2021)
Angiogenesis is essential for the development of tumors. Studies have shown that carcinoma-associated fibroblasts (CAFs) are involved in regulating tumor angiogenesis, but the mechanism remains unclear. Recently, long noncoding RNAs (lncRNAs) have been proved to play an important role in the angiogenesis of various tumors. However, there is currently no research involving the regulation of CAFs on the angiogenesis of oral squamous cell carcinoma (OSCC) mediated by lncRNAs. By analyzing microarray data, we identified that the expression of lncRNA FOXF1 adjacent noncoding developmental regulatory RNA (FENDRR) in OSCC patients is downregulated, compared to that in normal tissues. Quantitative polymerase chain reaction (qPCR) results demonstrated that FENDRR expression is lower in CAFs compared to normal fibroblasts (NFs) of OSCC patients. KEGG pathway analysis revealed that some genes differentially expressed between CAFs and NFs of HNSCC patients are enriched to the PI3K/AKT pathway. Further experiments confirmed that the downregulation of FENDRR can activate the PI3K/AKT pathway in NFs and enhances the expression of matrix metalloproteinase 9 (MMP9). The overexpression of FENDRR had the opposite effect. Besides, we co-cultured human umbilical vein endothelial cells (HUVECs) with CAFs, and the tube-forming ability of HUVECs co-cultured with CAFs overexpressing FENDRR decreased significantly. In summary, our experiments are focused on the influence of lncRNAs in CAFs on OSCC angiogenesis for the first time and prove that FENDRR mediates CAFs' regulation of OSCC angiogenesis through the PI3K/AKT pathway.